DEVELOPMENT OF GREEN FINANCE IN UZBEKISTAN IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Jiyanova N.E.; Alimkhonova G.E. (Innovation Science and Technology, 2025)
Green financing is a key mechanism for achieving sustainable development goals, providing investments in projects aimed at reducing carbon footprints, preserving ecosystems, and supporting the "green" transformation of the economy. In Uzbekistan, the development of green financing institutions and the use of various financial instruments play a crucial role in modernizing the economy and increasing its resilience amid ongoing reforms. This article explores the role of international and national green financing institutions, analyzes the growing application of green financing tools, and examines measures to overcome existing challenges and create conditions for the active implementation of green financing mechanisms in Uzbekistan.